The content of matrix metalloproteinase-1, -9 and tissue inhibitor of matrix metalloproteinase-1 in patients with bronchial asthma and obesity - V. V. Kachkovska; L. N. Prystupa (Patologìâ)
Airway remodeling is a significant factor in the progression of respiratory failure in bronchial asthma (BA). Obesity can contribute to inflammation, and consequently – airway remodeling, by increased production of matrix proteinase (MMP). However, the mechanisms of remodeling in different phenotypes of BA, especially in comorbid patients, remain poorly understood.